The Analysis of Students’ Digital Literacy Skills Level in Instructional Practice in English Department at Universitas Negeri Padang - Fathur Al Furqan; Rusdi Noor Rosa (Universitas Negeri Padang, 2023)
This thesis presents a quantitative research study that assesses the digital literacy skills level of students in the English Department at Universitas Negeri Padang, focusing on factors influencing their proficiency. The research findings reveal that the majority of students demonstrate a high level of digital literacy skills, with a significant proportion categorized as very good or good. However, only one student falls into the poor level category, indicating an overall positive digital literacy skills landscape among the participants. The study employs a quantitative research approach, utilizing surveys to collect data on students' Knowledge of Digital Literacy and factors affecting their ability to use it. The questionnaires provide insights into various factors that students perceive as hindrances to their digital literacy development. The analysis of the survey data identifies the main factors as follows: (1) lack of budget, (2) lack of supporting resources, (3) lack of environment, (4) lack of training opportunities, (5) lack of time, (6) lack of facilities, (7) lack of interest, (8) lack of learning materials, (9) lack of skills, and (10) lack of knowledge. These findings shed light on the challenges faced by students in developing their digital literacy skills and inform potential areas of improvement in instructional practice. Educators and policymakers can utilize this information to address the identified factors and create an environment conducive to enhancing students' digital literacy competencies.